The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00431-023-04822-7
|View full text |Cite
|
Sign up to set email alerts
|

Complications of one-step button percutaneous endoscopic gastrostomy in children

Abstract: To assess the complications of one-step button percutaneous endoscopic gastrostomy (B-PEG) and determine risk factors for developing stomal infections or gastropexy complications. MethodsA retrospective study of 679 children who underwent a B-PEG procedure in a single tertiary care center over a 10-year period to December 2020 was conducted. Patient characteristics, early complications (occurring ≤7 days after the procedure), late complications (> 7 days after the procedure), and outcomes were collected from m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The rate of T-fastener-related complications is significant and clearly a disadvantage of the technique. 8 10 20 We share the same clinical experience that optimal tightness and duration of the T-fasteners seem to decrease the complications. 10 In our department, the percutaneous and endoscopic push technique remains the primary method for gastrostomy placement, and laparoscopy is reserved for cases in which safety of this method is in doubt during the procedure.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The rate of T-fastener-related complications is significant and clearly a disadvantage of the technique. 8 10 20 We share the same clinical experience that optimal tightness and duration of the T-fasteners seem to decrease the complications. 10 In our department, the percutaneous and endoscopic push technique remains the primary method for gastrostomy placement, and laparoscopy is reserved for cases in which safety of this method is in doubt during the procedure.…”
Section: Discussionmentioning
confidence: 67%
“…The push technique was found to have the lowest rate of complications. In the largest retrospective series 8 including 679 children who underwent PEG with the push technique, the median follow-up time was 2.8 years and rates of major, early, and late complications were <2%, 15.9%, and 78.0%, respectively. In the aforementioned studies, complications have been reported non-uniformly, making comparison with our results challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations